Social influence as a new element of academic culture - reflections after the Ministerial Academic Debate Forum devoted to the third evaluation criterion (Ministry of Science and Higher Education). Diagnosis on the eve of assessment with practical applications in a social science context - Dagna Dejna (Journal of Modern Science)
The article discusses the issue of evaluating the scientific activities of universities. The article describes the third evaluation criterion and the method of qualitatively measuring the impact of scientific activity on the functioning of society and the economy. Author's reflections and analysis of literature supplemented with comments and shares of the Science and Higher Education application and data from the Science Evaluation Committee for 2019-2022. Additional information appears in connection with the SOWA (Social Circulations of Academic Knowledge) research network, which reconstructs key issues related to assessment III. Comments collected during the scientific and practical symposium conducted by the Ministry of Science and Higher Education on October 18, 2024, authored by this text composed of contributions. There are few articles about the third criterion. This is an area that is considered mysterious and risky by researchers. The work briefly describes the history of the strategy for evaluating scientific activities in Poland. The challenges faced by researchers who decide (or are forced) to conduct research aimed at applying the results to social reality are described in detail. The text describes the academic community's concerns about evaluating the social impact of research. Necessary changes in thinking about the role of the university were identified. The most urgent changes were also outlined, the introduction of which to the evaluation system of criterion III will result in greater interest in these issues.